THE ROLE OF FINANCIAL INCLUSION IN PROMOTING THE ASSET GROWTH OF A SAMPLE OF BANKS LISTED AT THE IRAQI STOCK EXCHANGE - ALI, MOWAFFAK AHMED; IBRAHIM, SARDAR SHAKER (Journal of Duhok University, 2023)
The purpose of this paper is to examine the extant role of financial inclusion at enhancing asset growth from a sample of 17 private banks in Iraq. Seventeen listed banks out of the existing forty-six private banks were selected for the study. The period of the study was 2010 to 2020. Multiple regression and Anova test were carried out to determine the impact of financial inclusion as independent variables through usage and access indicators and bank growth through asset growth as a dependent variable. The finding of this study indicates that the independent variables in this model explain only 2% of the variance in the dependent variable. Moreover, the null hypothesis will be rejected and the alternative hypothesis will be accepted which indicates that there is a significant effect of the independent variable (financial inclusion) on the dependent variable (asset growth) at the study's (0.05) level. The study recommends that Iraqi banks especially banks listed in the Iraq Stock Exchange should have an integrated network of banking branches, and their spread should be in a way that covers all regions of the country, no matter whether these outlets are electronic or human